Post‐stroke seizure—Do the locations, types and managements of stroke matter?. Issue 3 (31st July 2018) - Pande, Shrikant D.; Lwin, May Thiri; Kyaw, Kaung Myat; Khine, Aye Aye; Thant, Aye Aye; Win, May Myat; Morris, Julie
Summary: Objective: To determine the incidence of post‐stroke seizures and the associated risk factors in a government‐restructured hospital in Singapore. Methods: This retrospective study included consecutive patients (age ≥21 years) admitted to the stroke rehabilitation facility at Changi General Hospital, Singapore, between June 2008 and May 2017, with a minimum post‐discharge follow‐up of 6 months. Patients with known epilepsy central nervous system infection or tumor, a history of neurosurgery and or missing data were excluded from study. To determine the incidence of seizures, the patients' hospital records, including those for all initial and subsequent admissions and outpatient follow‐ups, were reviewed. All prescribed medications were checked and documented. Seizures were diagnosed on the basis of clinical examination with or without electroencephalography. Results: In total, 722 patients (women, 38%) with a mean age of 64 years were included. Of these, 48 (6.64%) experienced post‐stroke seizures during a follow‐up period of 6–108 months. The incidence of seizures was significantly higher in patients with hemorrhagic stroke (42%, p = 0.010), those with ischemic partial anterior circulation stroke (PACS) (27%, p = 0.025), those who underwent a neurosurgical procedure after stroke (p < 0.001), those with a low activated partial thromboplastin time (APTT) at admission (mean, 25.6; p = 0.015), and those using levodopa (21%, p < 0.001). Neurosurgical intervention after stroke (odds ratio [OR] 6.2, 95% confidence interval [CI] 2.9–13.1; p < 0.001), APTT (per‐unit increase; OR 0.86, 95% CI 0.76–0.98; p = 0.028), and underlying ischemic heart disease (IHD; OR 2.2, 95% CI 1.08–4.60; p = 0.029) were found to be independent predictors of seizure occurrence after stroke. Significance: Post‐stroke seizure incidence from our study is 6.64%, with a median follow‐up of 49 months. Among patients with stroke, those with underlying IHD, those who undergo a neurosurgical procedure, and those with a low APTT at admission need careful monitoring. Levodopa should be used with caution and withdrawn as soon as possible.